Oral cancer screening knowledge and practices among dental professionals at the University of Toronto - Mavedatnia, Dorsa; Cuddy, Karl; Klieb, Hagen; Blanas, Nick; Goodman, Jade; Gilbert, Melanie; Eskander, Antoine (Université d'Ottawa | University of Ottawa, 2023)
Abstract Introduction Opportunistic oral cancer screening during visits to the dentist is a non-invasive and accessible option for detection of pre-malignant lesions and early-stage malignancies. The objective of this study was to investigate the knowledge, practices, and attitudes towards oral cancer screening among dentists. Methods A 42-item survey was sent to 650 dental professionals affiliated with the University of Toronto. Data regarding training/practice characteristics, knowledge of oral cavity cancer, current screening practices, attitudes towards screening, and remuneration were collected. Results Ninety-one dentists responded. Most obtained their dental degree from Canada (71.4%) and were practicing in large urban centers (87.9%). Most dentists correctly identified the oral tongue (87.8%) and floor of mouth (80%) as the two of most common sites of oral cavity cancer but only 56% correctly identified the most common presentation. 91% performed intra/extra oral examinations at every patient visit. Only 9.9% of dentists discussed the risk factors of oral cancer and 33% were not familiar with resources for smoking cessation and alcohol abuse. International medical graduates were more likely to discuss risk factor management than Canadian medical graduates (p < 0.01). Over 80% of dentists referred to a specialist when a suspected lesion was found. The greatest barrier for oral cancer screening was lack of time. Almost all dentists (98.8%) reported that their screening practices do not differ depending on the patient’s insurance status and 63.8% reported compensation would not influence their decision to perform oral examinations. Conclusion Most dentists have a good knowledge of the presentation and risk factors associated with oral cavity cancer. Most dentists perform screening with every patient, with no influence from compensation and insurance status. Dentists are therefore an excellent first contact for oral cavity cancer screening for the general public and for high-risk populations.